Notary Criminal Liability against Authentic Deals Indicated to Criminal Actions (Case Study of Field High Court Decision Number: 82/PID/2010/PTMDN) - Zico Ricardo Aritonang (LEGAL BRIEF, 2022)
The Law on Notary Positions does not at all contain the concept of notary criminal responsibility. Whereas in practice in the field it is often found that a legal action or violation committed by a notary related to the authentic deed he made is qualified as a criminal act. criminalizing a notary by applying the articles of the Criminal Code without being preceded by an in-depth study of the concept of criminal liability of a notary is an act that cannot be justified scientifically and juridically. Therefore, efforts to formulate the concept of criminal liability of a notary is an important step that must be taken to avoid the symptoms of arbitrary criminalization of a notary as a public official.